2021
DOI: 10.1002/hep4.1716
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of De Novo Hepatocellular Carcinoma After Sustained Virologic Response

Abstract: Hepatocellular carcinoma (HCC) can de novo develop in patients with chronic hepatitis C even after the achievement of sustained virologic response (SVR). We characterized de novo HCC after SVR, comparing it with HCC that developed in patients during persistent hepatitis C virus (HCV) infection. Characteristics, survival rates, and recurrence rates after curative treatment in 178 patients who developed initial HCC after SVR diagnosed between 2014 and 2020 were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Unlike post-SVR HCC recurrence in patients with a history of HCC, post-SVR HCC in patients with no history of HCC, ie, de novo HCC, only modestly increased mortality after SVR. The survival rate of patients with de novo HCC after SVR was significantly higher than that of patients with HCC that developed during persistent HCV infection, 14 which was associated with a decreased unfavorable influence of post-SVR HCC on mortality in patients with no history of HCC. Consequently, patients with compensated cirrhosis and those without cirrhosis showed no difference in either liver-related or nonliver-related mortality after PSM.…”
Section: Discussionmentioning
confidence: 90%
“…Unlike post-SVR HCC recurrence in patients with a history of HCC, post-SVR HCC in patients with no history of HCC, ie, de novo HCC, only modestly increased mortality after SVR. The survival rate of patients with de novo HCC after SVR was significantly higher than that of patients with HCC that developed during persistent HCV infection, 14 which was associated with a decreased unfavorable influence of post-SVR HCC on mortality in patients with no history of HCC. Consequently, patients with compensated cirrhosis and those without cirrhosis showed no difference in either liver-related or nonliver-related mortality after PSM.…”
Section: Discussionmentioning
confidence: 90%
“…Liver function improved between initial HCC diagnosis and recurrence in these patients but declined in controls. SVR patients thus received more frequent curative treatment for recurrence (Toyoda et al, 2021). Montasser (2021) reported that tumor size in DAA-treated patients was statistically larger than in patients without a history of such treatment (p = 0.03), but types of intervention, BCLC stage, and survival had no impact (Montasser et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Three-year OS was 76% in DAA-HCC patients versus 88.93% in control HCC subjects (Brozzetti et al, 2021). Conversely, other studies found a higher survival rate in SVR achievers who developed de-novo HCC lesions during surveillance, despite similar recurrence rates after curative HCC management (Toyoda et al, 2021). Tumors were more extensive in patients that received DAA treatment, but no difference in survival was reported in another study (Montasser et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…This might be because of poor awareness regarding the risk of HCC in patients without viral hepatitis, and, more importantly, difficulty in identifying patients with non-viral liver diseases who are at risk of HCC and who should, therefore, undergo HCC surveillance.Assessment with the ALBI score showed that liver function at HCC diagnosis improved over time in both groups, and this improvement was greater in the viral HCC group than in the non-viral HCC group. In the viral HCC group, the clinical use of oral antiviral therapy for HBV infection (nucleos[t]ide analogues, NAs) and for HCV (direct-acting antivirals, DAAs) contributed to preventing liver function deterioration over the course of chronic infection, resulting in an increase in the percentage of patients with better liver function at the development of HCC 10. Whereas NAs for HBV were available and used in most patients throughout the study period, the percentage of HCV patients who achieved SVR increased significantly over time due to the emergence of DAAs.…”
mentioning
confidence: 99%